Digitalizing Sanad: A Virtual Ethnography of Zoom-Based Qira'at Learning Communities in Post-Pandemic Indonesia - Romlah Widayati (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2026)
This study analyzes the transformation of the qira’at (Qur'anic recitation) study tradition after the Covid-19 pandemic through Zoom-based learning communities in Indonesia, focusing on changing patterns of learning interaction, the preservation of sanad, and the formation of a digital religious culture. While previous research on online Qur'anic learning has largely addressed pedagogical effectiveness, tahfiz, and virtual maqra'ah, the question of how the authority and legitimacy of sanad are renegotiated when talaqqi moves into virtual space remains under-examined; this article addresses that gap. The study uses a qualitative field-research method with a virtual-ethnographic design, informed by Hine's virtual ethnography and Campbell's digital-religion framework. Data were obtained through participant observation of online halaqah, semi-structured interviews with twenty informants (sanad-holding qira’at teachers, Ulumul Qur'an lecturers, and community members from several regions of Indonesia), and digital documentation in the form of Zoom recordings and learning archives. Data were analyzed using the interactive model of Miles and Huberman through data condensation, data display, and conclusion drawing, with source, method, and time triangulation. The findings show that Zoom-based qira’at communities sustain the traditions of talaqqi and scholarly sanad through the adaptation of digital technology, expand access for women and working professionals, and cultivate cross-regional spiritual solidarity. Rather than claiming a wholesale new paradigm, the study reads these practices as a form of mediated talaqqi, in which sanad continuity is preserved while its documentary and spatial form is reconfigured. The study concludes that the digitalization of qira’at is best understood not as a replacement of tradition but as an adaptive extension integrating sanad, spirituality, and digital technology, whose long-term theological legitimacy still requires further scholarly and juristic evaluation.